2019
DOI: 10.34133/2019/7937156
|View full text |Cite
|
Sign up to set email alerts
|

instaGraminoid, a Novel Colorimetric Method to Assess Herbicide Resistance, Identifies Patterns of Cross-Resistance in Annual Ryegrass

Abstract: Herbicide resistance in agricultural weeds is a global problem with an increasing understanding that it is caused by multiple genes leading to quantitative resistance. These quantitative patterns of resistance are not easy to decipher with mortality assays alone, and there is a need for straightforward and unbiased protocols to accurately assess quantitative herbicide resistance. instaGraminoid—a computer vision and statistical analysis package—was developed as an automated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Reducing the assessment delay and reliance on visual estimates would improve repeatability and efficiency of the process. Computer vision tools and machine learning for image‐contextual understanding may offer opportunities to identify seedling chlorosis and necrosis 77 . On an individual plant assessment level, analysis of red‐green‐blue colour images of L. rigidum seedlings at 0, 7‐ and 14‐day intervals post‐treatment with glyphosate, sulfometuron, terbuthylazine and trifluralin, correctly classified 95% of the treated plants as either resistant or susceptible 77 .…”
Section: Improving Herbicide Resistance Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the assessment delay and reliance on visual estimates would improve repeatability and efficiency of the process. Computer vision tools and machine learning for image‐contextual understanding may offer opportunities to identify seedling chlorosis and necrosis 77 . On an individual plant assessment level, analysis of red‐green‐blue colour images of L. rigidum seedlings at 0, 7‐ and 14‐day intervals post‐treatment with glyphosate, sulfometuron, terbuthylazine and trifluralin, correctly classified 95% of the treated plants as either resistant or susceptible 77 .…”
Section: Improving Herbicide Resistance Surveysmentioning
confidence: 99%
“…Computer vision tools and machine learning for image‐contextual understanding may offer opportunities to identify seedling chlorosis and necrosis 77 . On an individual plant assessment level, analysis of red‐green‐blue colour images of L. rigidum seedlings at 0, 7‐ and 14‐day intervals post‐treatment with glyphosate, sulfometuron, terbuthylazine and trifluralin, correctly classified 95% of the treated plants as either resistant or susceptible 77 . When trained on glyphosate‐treated plants and tested on unseen glyphosate‐treated test sets, the model correctly classified 100% of plants.…”
Section: Improving Herbicide Resistance Surveysmentioning
confidence: 99%
“…Chloroplast integrity is compromised, and vegetative tissue loses green pigment (Carter 1993; Major et al 2003). Chlorophyll content and spectral reflectance are correlated; thus, PPO-inhibiting herbicide-treated plants could be imaged and analyzed to detect differences in spectral reflectance and thus confirm resistance (Gitelson et al 2003a; Major et al 2003; Paril and Fournier-Level 2019). Previous research has demonstrated that spectral reflectance can discriminate between herbicide-treated plants, weed species, and herbicide-resistant weed biotypes (Everman et al 2008; Reddy et al 2014; Sanders et al 2021; Zhao et al 2014).…”
Section: Introductionmentioning
confidence: 99%